Left hippocampus sparing whole brain radiotherapy (WBRT): A planning study - Kazda, Tomas; Vrzal, Miroslav; Prochazka, Tomas; Dvoracek, Petr; Burkon, Petr; Pospisil, Petr; Dziacky, Adam; Nikl, Tomas; Jancalek, Radim; Slampa, Pavel; Lakomy, Radek (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2017)
AIMS: Unilateral sparing of the dominant (left) hippocampus during whole brain radiotherapy (WBRT) could mitigate cognitive decline, especially verbal memory, similar to the widely investigated bilateral hippocampus avoidance (HA-WBRT). The aim of this planning study is dosimetrical comparison of HA-WBRT with only left hippocampus sparing (LHA-WBRT) plans. METHODS: HA-WBRT plans for 10 patients were prepared in accordance with RTOG 0933 trial and served as baseline for comparisons with several LHA-WBRT plans prepared with an effort: 1) to maintain the same left hippocampus dosimetry ("BEST PTV") and 2) to maintain same dosimetry in planning target volume as in HA-WBRT ("BEST LH"). RESULTS: All HA-WBRT plans met RTOG 0933 protocol criteria with a mean Conformity index 1.09 and mean Homogeneity index (HI) 0.21. Mean right and left hippocampal D100% was 7.8 Gy and 8.5 Gy and mean Dmax 14.0 Gy and 13.8 Gy, respectively. "BEST PTV" plans reduced HI by 31.2% (P=0.005) which is mirrored by lower PTV_D2% (-0.8 Gy, P=0.005) and higher PTV_D98% (+1.3 Gy, P=0.005) as well as decreased optic pathway's Dmax by 1 Gy. In "BEST LH", mean D100% and Dmax for the left hippocampus were significantly reduced by 11.2% (P=0.005) and 10.9% (P=0.005) respectively. CONCLUSIONS: LHA-WBRT could improve target coverage and/or further decrease in dose to spared hippocampus. Future clinical trials must confirm whether statistically significant reduction in left hippocampal dose is also clinically significant.
Keywords: Brain Neoplasms; dávka záření; Organs at Risk; cognition; Retrospective Studies; hipokampus; Radiotherapy Dosage; celková dávka radioterapie; Middle Aged; hippocampus; mužské pohlaví; léčba šetřící orgány; brain metastases; ženské pohlaví; retrospektivní studie; Humans; Radiation Dosage; plánování radioterapie pomocí počítače; lidé středního věku; nádory mozku; Organ Sparing Treatments; kritické orgány; memory; Female; HA WBRT; lidé; Male; Hippocampus; Radiotherapy Planning, Computer-Assisted